2003
DOI: 10.1021/cm021048+
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a New Cyclotriphosphazene-Terminated Perfluoropolyether Lubricant. Properties and Interactions with a Carbon Surface

Abstract: A novel perfluoropolyether (PFPE) structure terminated on one chain end by a hydroxyl end group and on the other end by a cyclotriphosphazene derivative was studied. The interactions that developed at the interface between molecularly thin films of this material (A20H) and amorphous nitrogenated carbon surfaces were investigated using contact angle goniometry, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and imaging ellipsometry. The results demonstrate that both the cyclotriphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The peak at 814 amu is assigned to (CF 3 -C 6 H 4 -O-) 4 , F(NP) 3 -O -. It is believed to be generated when F -replaces a phenoxy group on one of the phosphorus atoms.…”
Section: A20h and C2: Tof-sims Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at 814 amu is assigned to (CF 3 -C 6 H 4 -O-) 4 , F(NP) 3 -O -. It is believed to be generated when F -replaces a phenoxy group on one of the phosphorus atoms.…”
Section: A20h and C2: Tof-sims Studymentioning
confidence: 99%
“…Consequently efforts were made to chemically link the cyclotriphosphazene moiety to the PFPE molecular chain and led to development of the lubricant A20H [4]. Shown below are the formulae of X1P and A20H.…”
Section: Introductionmentioning
confidence: 99%
“…3. Here A20 is a derivative of Z-dol in which one of the hydroxyl end-groups is replaced by a cyclotriphosphazene [7]. It is clearly revealed that those lubricants photo-grafted are indeed strongly bound.…”
Section: Grafting Pfpe Chains By the Maya Processmentioning
confidence: 99%
“…A mixture of Z-dol and X1P, however, has a miscibility issue. The PFPE lubricant receiving topical attention, known by the brand name A20H, is a derivative of Z-dol having an X1P-like cyclotriphosphazene unit attached to one end and retaining the original hydroxyl unit at other end [11]. It may be an ideal lubricant meeting all the requirements listed above.…”
Section: Summary and Commentsmentioning
confidence: 99%